Systems biology graphical notation (SBGN) - Mi, Huaiyu (Henry Stewart Talks, 2014)
History & motivations for using SBGN, Pathway pipelines today, Systems approach in bioscience research, Ontology in biological knowledge, Gene ontology (GO) representations, EcoCyc (the first pathway database), Pathway standards and network diagrams, Diagrams generated by computer vs. biologists, Ambiguity in conventional representation, Kohn's molecular interaction maps (MIM), Kitano's process diagram notation, Orthogonal projection of biology, SBGN symbols & rules, Process descriptions (PD), Entity relationships (ER) & Activity flow (AF), Computational modelling in biology network (COMBINE)